Interventions used by health professionals in older adults with low levels of health literacy: a scoping review - Helenice de Moura Scortegagna; Meire Cachioni; Sheila Cristina Cecagno-Zanini; Vanessa Alonso; Ruth Caldeira de Melo; Anita Liberalesso Neri (Brazilian Society of Geriatrics and Gerontology, 2023)
This scoping review sought to identify, synthesize, and assess the available evidence on the aims and effects of interventions used by health professionals in older adults with low levels of health literacy. Relevant articles were selected from the databases from April 2017 to April 2020. The Joanna Briggs Institute Manual for Evidence Synthesis was used for conducting this scoping review, and a total of 22 studies were reviewed. The positive effects observed for each type of intervention, yielding significant results for some of the outcomes and improvements in intragroup scores, demonstrated that the interventions had good acceptability by older adults with limited health literacy. However, we were not able to determine which intervention strategies had a significant positive effect on health outcomes in these patients. Further high-quality randomized clinical trials employing greater methodological rigor for assessing results are needed to elucidate the potential benefits of interventions in this population.